Biofluid mechanics in cardiovascular systems - Waite, Lee (McGraw-Hill's biomedical engineering series, 2006)
Biofliudics has gained in importance in recent years, forcing engineers to redefine mechanical engineering theories and apply them to biological functions. To date, no book has successfully done this. Biofliud Mechanics in Cardiovascular Systems is one of the first books to take an interdisciplinary approach to the subject. Written by a professor and researcher, this book will combine engineering principles with human biology to deliver a text specifically designed for biomedical engineering professionals and students.